Gender Bias and the Journal of Roman Studies: JRS EDITORIAL BOARD. (November 2019) - Kelly, Christopher; Thonemann, Peter; Borg, Barbara; Hillner, Julia; Lavan, Myles; Morley, Neville; Mullen, Alex; Orlandi, Silvia; Pillinger, Emily; Prag, Jonathan; van der Blom, Henriette; Whitton, Christopher
Abstract : Reflecting on present unease about structural biases in the discipline, and aiming to offer a data-rich response to some recent criticisms of this Journal, the Editorial Board has undertaken a study of the representation of female scholars in the Journal of Roman Studies . To that end, we have gathered data on publications, submissions and JRS Editorial Board membership for the past fifteen years, from Volume 95 (2005) through to the present volume, Volume 109 (2019). The data are set out in the final section (VII), following a brief review of the main results. Our goal here is neither to present a definitive analysis, nor to offer a commentary on the underlying causes of the patterns revealed (on which we expect much fruitful discussion elsewhere). Rather, the JRS Editorial Board aims to make key data available both to inform a much wider debate within the profession as a whole and, importantly, to inform this Journal 's policies, procedures and active outreach. The Board is also acutely aware that any analysis of gender bias needs to be framed carefully — both by an awareness that there are other under-represented groups in the discipline (on which our data in their current form would regrettably only offer a most imperfect picture), and by a sensitivity to the limitations of a conception of gender as a simple binary.